Causes of Menorrhagia and Its Pathological Diagnosis by Dilatation and Curettage - Shaheen, Shagufta; Akhtar, Shahnaz; Utman, Naeema (Journal of Postgraduate Medical Institute, 2011)
to find out the causes of menorrhagia and role of diagnostic dilatation and curettage. This prospective study was conducted in department of Obstetric and Gynae LRH, Peshawar from first January to December 1997. One hundred and twenty one patients with menorrhagia were studied. The age range was between 21 - 40 years. Full investigations for the causes of menorrhagia were carried out. All the patients having menstrual blood loss of more than 8 days or history of passage of clots or having hemoglobin less than 10mg/dl were included in the study and patients having pubertal menorrhagia less than 20 eyars were excluded. All patients having menorrhagia during reprductive age and above 40 years should be screened for any endometrial pathology. Accurate analysis of endometrial sampling is the key to effective therapy and optimal outcome.